The Mobius framework and its implementation. - Deavours, D.D.
The Mobius framework is an environment for supporting multiple modeling formalisms and solution techniques. Models expressed in formalisms that are compatible with the framework are translated into equivalent models using Mobius framework components. This translation preserves the structure of the models, allowing efficient solutions. The framework is implemented in the tool by a well-defined abstract functional interface. Models and solution techniques interact with one another through the use of the standard interface, allowing them to interact with Mobius framework components, not formalism components. This permits novel combinations of modeling techniques, and will be a catalyst for new research in modeling techniques. This paper describes our approach, focusing on the "atomic model". We describe the formal description of the Mobius components as well as their implementations in our software tool.
Keywords: Markov models; Mobius framework; PEPA; Abstract functional interface; Equivalent models; Execution policy; Formal description; Modeling tools; Multiple modeling formalisms; Software tool; Stochastic Petri nets